Językoznawcze zainteresowania Józefa Ignacego Kraszewskiego - Sokólska , Urszula (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article is devoted to the linguistics interests of Józef Ignacy Kraszewki who views language as a complex lexical, syntactic and semantic structure rather than merely the matter used for creating a literary vision of the world. The subjects of the detailed analysis are the journalistic and quasi-linguistic texts published in Studia literackie (Literary studies) and Nowe studia literackie (New literary studies) which discuss the relics of the Polish language’s past and the development of its vocabulary, with particular focus on the status of loanwords, neologisms and archaisms from various stages of the development of the Polish language. The image that emerges from the analysed texts is one of a writer-linguist who perfectly understands the mechanisms that rule language and who shows that language is dynamic and changes due to the needs of its users and all possible external factors.